ChemInform Abstract: Metallasilsesquioxanes: Molecular Analogues of Heterogeneous Catalysts. Issue 12 (14th March 2013) - Ward, Antony J.; Masters, Anthony F.; Maschmeyer, Thomas
Abstract Review: 55 refs.